‘Is Ethnicity the Root of all Evil?’ Engaging Macro and Micro Analysis of Ethnic Violence in Post New-order Indonesia - Zein, Rizqy Amelia (Political Science Program, Universitas Negeri Semarang, 2018)
In this theoretical review, the author examines intergroup conflicts and genocides in post New-Order Indonesia as the manifestation of politicised nationalism by employing several theoretical approaches. The theoretical review starts from combining micro (social-psychological approach) and macro perspectives (sociological and political approach) to answer these following questions; (a) how do we explain intragroup conflicts and genocides, especially in post New-Order Indonesia, as the consequences of nationalism’s existence? (b) In what circumstances are intergroup conflict, or in the most extreme case; genocide, likely to occur? Thus, the theoretical review is structured into four parts; addressing the problem of intergroup conflict and genocide as well as emphasising its importance to be aware of; tracing back the emergence of the nation using Smith and Barthian’s ethno-symbolic approach; narrating the conditions in which allow intergroup conflict arose; and some concluding remarks.